2013
DOI: 10.1002/jor.22332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise level on biomarkers in a rat knee model of osteoarthritis

Abstract: The aim of this study was to elucidate whether the levels of serum biomarkers reflect the progression of osteoarthritis (OA) induced by different levels of exercise. Thirty-five Wistar rats subjected to anterior cruciate ligament transaction (ACLT) were divided into three groups: Control, moderate running, and intense running. Twelve rats (moderate running without ACLT) were allocated as a naive group. Running was performed on a motorized treadmill, at a speed of 18 m/min for 30 min/day (moderate and naive) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…PGC-1α induces the production of mitochondria and synthesis of slow contractile proteins [16]. It was reported that PGC-1α activation plays an important role in up-regulating the formation of slow muscle fibers [17,18]. Slow muscle fibers expression and PGC-1α protects against muscle atrophy due to the inhibition of atrogenes [18,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGC-1α induces the production of mitochondria and synthesis of slow contractile proteins [16]. It was reported that PGC-1α activation plays an important role in up-regulating the formation of slow muscle fibers [17,18]. Slow muscle fibers expression and PGC-1α protects against muscle atrophy due to the inhibition of atrogenes [18,20].…”
Section: Discussionmentioning
confidence: 99%
“…Peroxisome proliferator-activated receptor-γ coactivatior-1α (PGC-1α) is expressed in several tissues, including skeletal muscle and brown adipose tissue [16]. It has been shown that transcriptional co-activator PGC-1α increases the formation of slow muscle fibers [17,18]. PGC-1α is expressed in skeletal muscle, and induces mitochondrial biogenesis as well as activity of the myoglobin [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The method was in accordance to the procedure described by [27] for plasma and urine measure, respectively. Plasmatic levels of CPII, the carboxyl propeptide of type II procollagen, were also evaluated by ELISA assay (Ibex, Canada) according to [28,29]. …”
Section: Methodsmentioning
confidence: 99%
“…19 In ACLT model, serum level of C2C, a biomarker of type II collagen degradation, was decreased by moderate running on a motorized treadmill (at a speed of 18 m/min for 30 min/d, 3 days per week) while the serum level of CPII, a biomarker of type II synthesis, was decreased by intense running (at a speed of 18 m/min for 60 min/d, 3 d/wk) 2 and 4 weeks after surgery. 20 In addition, in all the groups at 2 and 4 weeks after surgery, the Osteoarthritis Research Society International (OARSI) histological score was slightly but significantly correlated positively with the C2C/ CPII ratios. 15 In ACLT rats, serum CTX-II and COMP levels were increased and only CTX-II correlated with the modified Mankin score.…”
Section: Ratsmentioning
confidence: 98%